“I've Always Thought That I Was Not Good at Experiments…”—The Benefit of Non-formal Learning in Terms of Students' Perceived Competence - Kirchhoff, Tim; Wilde, Matthias; Großmann, Nadine (Frontiers in Psychology, 2022)
Outreach science labs have been established as non-formal out-of-school learning environments in the fields of science, technology, engineering, and mathematics. Previous research has suggested that visiting an outreach science lab can be beneficial in terms of student motivation. Nevertheless, the current research on these out-of-school learning environments lacks studies that investigate important variables for the development of self-determined student motivation, such as perceived competence. In our study, we investigated the moderating effect of the learning environment on the relationship between students’ contextual competence perceptions and their situational competence experiences regarding experimentation. For this purpose, 119 students in the first year of the upper secondary school participated in an experimental course on enzymology at an outreach science lab (n = 60) and in their biology classroom at school (n = 59). Our results showed that the relationship between students’ contextual competence perceptions and their situational competence experiences during experimentation is moderated by the learning environment. The analyses revealed that students with a higher contextual competence perception showed comparable situational experiences of competence in both learning environments. In contrast, the students who perceived themselves as less competent at a contextual level benefited from experimenting at the outreach science lab in terms of their situational competence experiences.